(3oZQQ GdaQGFO hoOQQ GdbdGFOs - (3Ydj Hf GdMSjf Hf ehSi Hf eMeO Hf EHQGgje, CHh GdbGSe ; GdTQja GdeQJVj,J (B436 (3g` s ((3MjOQ Hf jMji Hf GdMSjf GdTfjJj s)
(3ChdgG (B:s
(3bGd Gddg JHGQc hJYGdi(B: "(3hjSCdhfc Yf GdQhM, obd GdQhoM ef CeQ QHj, heG oChJjoJe ef GdYde EdG bdjdG(B" s
(3BNQgG (B:s
(3hgPG HNdGa eG Ydjg CcKQ GdfGS ef eQGYGI CeQ GdMGVQ GdbQjH, hEgeGd Mb GdHYjO s
(3GdfSNI HgG MhGTs
(3JJab aj ChdgG eY GdfSNI GdChdis
(3fSNI KGfjIs
(3aj CQHYI CLRGAs
(3hoCdMb HgG JcedI GdeDda ddCeGdj aj fMh KdGKjf hQbI s
(3bQf GdfSN (B:s
Keywords: (3GdCOHs